Human Resource Management Strategy in Improving Organizational Performance in the Industrial Era 4.0: Theoretical Perspectives and Strategic Implications - Muslimat, Ade (Doctoral Program of Social Science Pasundan University, 2024)
Rapid technological developments in the Industrial Era 4.0 have had a significant impact on various aspects of life, including the world of work and human resource management (HR). In facing this challenge, organizations need to formulate HR management strategies that can support improved organizational performance. This article aims to examine effective HR management strategies in improving organizational performance in the Industrial Era 4.0. The method used in this study is a qualitative approach with literature study analysis and in-depth interviews with HR practitioners in several leading companies. The strategies discussed include improving employee skills and competencies through technology-based training, implementing data-based management systems to improve operational efficiency, and creating an organizational culture that is adaptive to technological changes. In addition, the use of digital technology such as artificial intelligence and automation is also a key factor in increasing productivity and facilitating strategic decision-making related to HR management. The results of the study show that implementing the right HR management strategy can significantly improve organizational performance, create competitive advantages, and help organizations adapt quickly to changes in the digital era. Thus, organizations need to adapt quickly and effectively in managing HR to achieve sustainable long-term goals.